What Does Leadership Look like in Schools and Does It Matter for School Performance? - Lucy Stokes; Alex Bryson; David Wilkinson (Institute of Labor Economics (IZA), 2019)
We consider the role played by school leaders in improving pupil attainment, going beyond previous studies by exploring the leadership roles of deputy and assistant heads and classroom-based teachers with additional leadership responsibilities. Using panel data for state-funded secondary schools in England for the period 2010/11-2015/16 we find academy schools typically employ more staff in leadership roles than community schools. Increases in the number of staff in leadership roles below headship level are associated, at least to some extent, with improved school performance in Single Academy Trusts, but this is not the case for schools that are part of Multi Academy Trusts. Our findings suggest that the potential benefits of distributing leadership within schools may only be realised when leaders have sufficient autonomy.
Keywords: I21; 330; school performance; distributed leadership; leadership; school autonomy